Assessment of the efficacy and safety of fluticasone propionate and salmeterol delivered as a combination dry powder via a capsule-based inhaler versus a multi-dose inhaler in patients with chronic obstructive pulmonary disease. (April 2017) - Chan, Robert; Sousa, Ana R.; Hynds, Peter; Homayoun-Valiani, Farshid; Edwards, Dawn; Tabberer, Maggie
Abstract: Background: This study tested the clinical non-inferiority of the fluticasone propionate/salmeterol combination 50/250 μg (FSC) Rotacaps ® /Rotahaler ® system, a single unit dose inhaler, with the multi-dose FSC Diskus ® inhaler in adults with chronic obstructive pulmonary disease (COPD). Methods: This multi-centre, randomised, double-blind, double-dummy, two-way cross-over study compared 12 weeks' treatment of FSC administered twice daily using Rotacaps/Rotahaler or Diskus. The primary endpoint was change from baseline in trough morning forced expiratory volume in 1 s (FEV1 ) at Day 85, and the pre-defined non-inferiority criteria was: the lower limit of the confidence interval (CI) for the treatment difference (Rotacaps/Rotahaler-Diskus) in least squares (LS) mean change from baseline, being greater than −45 mL. Secondary endpoints included change in breathlessness (as measured by transition dyspnoea index (TDI)) and COPD-specific health status measures. Results: The LS mean increase from baseline in trough FEV1 at Day 85 was 116 mL in the Rotacaps/Rotahaler group and 91 mL in the Diskus group (difference in model-adjusted LS mean change: 25 mL (95% CI 2 mL, 47 mL)), the lower limit of the CI for the treatment difference being greater than the protocol-defined criterion for non-inferiority i.e. −45 mL. Data for breathlessness, COPD-specific health status and safety parameters were similar following FSC treatment via either inhaler. Conclusions: This study demonstrated the clinical non-inferiority of FSC 50/250 μg when administered using Rotacaps/Rotahaler compared with Diskus in patients with COPD. The risk:benefit profile for the two inhalers was comparable.